The critical issues of adopting halal logistics services - Kasim, Siti Roziana; Ali, Azizah; Ishak, Mohd Fikri; Mohd Sharif, Kamal Imran (2017)
Halal is in the nature of business and trade, and is becoming a global symbol for quality assurance and lifestyle choice.The primary issue is thousand of products and services produced at the global level have different of Halalization process such as symbolism, logo and certification from countries such as Malaysia, Australia, Singapore, Indonesia and China.Segregation of Halal and non-Halal food products must be highly practiced to avoid contamination.Although Halal is booming and on an upward trend, there are very limited studies published on Halal logistics and academic research in this area is highly needed.This study aim to investigate the issues of companies to get the Halal certification, finance capacity of company and the government support towards Halal logistics company.This study is examined in the case of Halal logistics in Kedah.Results obtained from this study uncover the various issues faced by Halal logistics service providers and are categorized into three critical issues. (BARRIER 1) Halal certification issue, (BARRIER 2) Government support issue, (BARRIER 3) Financial issue.The data was collected via an interview and primary source was used. The respondents are from middle management in Halal logistics company. This study is exploratory in nature and data are collected through series of focus group interviews and process with narrative analysis.The researcher managed to underline the research limitation such as the lack of empirical evidence, lack respondents from non-logistics companies and the study only focuses on Halal logistics thus ignoring other Halal businesses such as Halal pharmaceutical and Halal tourism.Plus, the issues uncovered open more doors for potential future research on barriers and critical success factors in adopting Halal into logistics management.